2021
DOI: 10.1002/ajmg.a.62483
|View full text |Cite
|
Sign up to set email alerts
|

Gain in growth after surgical repair of congenital heart disease among children with Down syndrome

Abstract: Down syndrome (DS) is a common genetic disorder among Saudi children, for which limited data is available on growth for those who undergo surgery for congenital heart disease (CHD). We assessed the magnitude of growth over time following surgery and the factors associated with growth change. Eighty-eight children with DS and CHD who underwent surgery between 2009 and 2017 at the tertiary children's hospital in Al-Qassim, Saudi Arabia, were eligible. Information on gender, height, and weight (at surgery, 6 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“… 19 The gain of growth was observed in children who underwent cardiac surgery/intervention. 31 Concomitant with this data, we found that weight and height SD were improved significantly 1 year after surgery ( Table 4 ).…”
Section: Discussionsupporting
confidence: 65%
“… 19 The gain of growth was observed in children who underwent cardiac surgery/intervention. 31 Concomitant with this data, we found that weight and height SD were improved significantly 1 year after surgery ( Table 4 ).…”
Section: Discussionsupporting
confidence: 65%